2021
DOI: 10.18632/aging.203137
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against focal cerebral ischemia-reperfusion injury in diabetic mice by ameliorating mitochondrial impairments: involvement of the Akt-SIRT3-SOD2 signaling pathway

Abstract: Diabetic patients are more vulnerable to cerebral ischemia-reperfusion (CIR) injury and have a worse prognosis and higher mortality after ischemic stroke than non-diabetic counterparts. Melatonin can exert neuroprotective effects against CIR injury in nondiabetic animal models. However, its effects on diabetic CIR injury and the underlying mechanisms remain unclarified. Herein, we found that melatonin administration improved neurological deficit, cerebral infarct volume, brain edema, and cell viability, reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 83 publications
(104 reference statements)
0
18
0
Order By: Relevance
“…Cytochrome c release and mitochondrial membrane disruption are intracellular events associated with apoptosis and often act as direct apoptotic drivers 42 . Our data suggest that PCC1 treatment enhanced cytochrome c release from mitochondria to the surrounding cytoplasmic space (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cytochrome c release and mitochondrial membrane disruption are intracellular events associated with apoptosis and often act as direct apoptotic drivers 42 . Our data suggest that PCC1 treatment enhanced cytochrome c release from mitochondria to the surrounding cytoplasmic space (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin appears to increase the activity of antioxidant enzymes such as SOD and GPX, through Sirtuin (SIRT)-3 [ 175 ]. Resveratrol is a phytoalexin derived from grapes [ 176 ], likely acting via several mechanisms: the downregulation of NOX expression and activity, mitochondrial O 2 •− reduction [ 177 , 178 ], and increased PON1 activity ( Figure 4 A).…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Many studies have confirmed the ability of melatonin to reduce damage to key mitochondrial constituents including proteins of the ETC and the mitochondrial genome [65,168,169], which normally appears under conditions of high oxidative stress. Melatonin's ability to stimulate mitochondrial superoxide dismutase 2 (SOD2) follows its deacetylation signaled by upregulation of the major mitochondrial deacetylase, SIRT3 [168,170,171].…”
Section: Melatonin In Mitochondria: Relation To Oxidative Stress and ...mentioning
confidence: 99%